The burden of road traffic injuries in Iran and 15 surrounding countries: 1990-2016 - Bazargan-Hejazi, S; Ahmadi, A; Shirazi, S; Ainy, E; Djalalinia, S; Fereshtehnejad, S-M; Jahanmehr, N; Kiadaliri, A; Moradi-Lakeh, M; Parsaeian, M; Pourmalek, F; Rahimi, K; et al. (Academy of Medical Sciences, I.R. Iran, 2018)
Background: The Global Burden of Disease (GBD) Study provides estimates of deaths, years of life lost (YLL), years of life lived with disability (YLD), and disability-adjusted life years (DALYs) due to 249 causes of death, 315 diseases and injuries, and 79 behavioral, environmental, occupational, and metabolic risk factors in 195 countries, territories, and regions by sex and 20 age categories in 195 countries and regions since 1990. In this study, we aimed to present the burden of road traffic injuries (RTIs) in Iran and 15 surrounding countries in 1990–2016.